2015
DOI: 10.1094/phyto-08-14-0213-r
|View full text |Cite
|
Sign up to set email alerts
|

Sr36- and Sr5-Mediated Resistance Response to Puccinia graminis f. sp. tritici Is Associated with Callose Deposition in Wheat Guard Cells

Abstract: Race-specific resistance of wheat to Puccinia graminis f. sp. tritici is primarily posthaustorial and often involves the induction of a hypersensitive response (HR). The aim of this study was to investigate host defense responses induced in interactions between P. graminis f. sp. tritici races and wheat lines carrying different race-specific stem rust resistance (Sr) genes. In incompatible interactions between wheat lines carrying Sr36 in three genetic backgrounds (LMPG, Prelude, or W2691) and avirulent P. gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
4
6
0
Order By: Relevance
“…Our results showed that callose depositions were mainly detected in guard cells. In support of our observations, Wang et al (2015) demonstrated that the resistance response to Puccinia graminis f. sp. tritici is associated with callose deposition in the wheat guard cells.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that callose depositions were mainly detected in guard cells. In support of our observations, Wang et al (2015) demonstrated that the resistance response to Puccinia graminis f. sp. tritici is associated with callose deposition in the wheat guard cells.…”
Section: Discussionsupporting
confidence: 90%
“…tritici pathosystem, during this interaction the resistance gene RPG1 was expressed a few minutes after inoculation with stem rust races (Nirmala et al 2010). More recently, in the same pathosystem it was observed early responses to avirulent stem rust races in wheat carrying resistance genes Sr5 and Sr36 involved callose deposition in stomatal guard cells (Wang et al 2015). It is possible that the genes identified here as induced in early hours in HdT may trigger a rapid and efficient response for the plant defense, and these mechanisms may involve pre-haustorial resistance in coffee-H. vastatrix interaction, in the same way found for barley and wheat pre-haustorial defense to P. graminis.…”
Section: Profiling Of Differentially Expressed Genes (Degs)mentioning
confidence: 92%
“…HR is reported to usually involve the death of host mesophyll cells, after the development of haustoria [19]; however, others have also observed pre-haustorial resistance responses in incompatible, ETI-mediated interactions. For example, a pre-haustorial response to stem rust was recently reported by Wang et al [20], who observed that early responses to avirulent stem rust races in wheat carrying resistance genes Sr5 and Sr36 involved callose deposition in stomatal guard cells. Another notable example of a pre-haustorial response to wheat stem rust is the case of barley durable stem rust resistance gene Rpg1 , which encodes a receptor-like kinase (RLK) that is autophosphorylated within minutes of inoculation with the avirulent pathogen [21, 22].…”
Section: Discussionmentioning
confidence: 89%